Costs related to immunopreventable diseases: Brazil and its geographic areas (immunopreventable diseases' costs in Brazil) - Élide Sbardellotto M. da Costa; Adriano Hyeda; Eliane M. C. P. Maluf (BMC, 2021)
Abstract Introduction The occurrence of the immunopreventable diseases in a population global reality. Objective To discriminate the direct costs of the hospitalizations from the immunopreventable diseases in the Unified Health System (SUS), in Brazil and their areas, between 2008 and 2018. Methods A population, observational, descriptive and retrospective study, with data from the information supplied by the DATASUS website, these data were collected during the 2019. Results It was identified 457,479 hospitalizations in the period; with a total of 2,450,870 days of hospital stay, with total costs of R$389,243,264.85. Only the disease mumps presented a growing tendency in whole areas; the chickenpox was decreasing; the illness whooping cough, yellow fever and tetanus were stationary in this period. Conclusions The costs related to immunopreventable diseases were relevant in all the Brazil areas, with tendencies different between the geographic areas and between the several illnesses analysed.